C.1 - Prasad, T. Krishna (Delhi, 2006)
This book is about debunking existing myths, an eye revealer to reality, based on the evidence based information by none less than an experienced law enforcement personnel, which gives so much credibility to the data. The mapping of the problem of trafficking through qualitative indicators of mul tiple vulnerabilities helps in looking at the problem compre hensively. Importantly, the understanding of trafficking from the perspective of social failures and costs helps in locating the primary responsibility of security of women and chil dren on society at large. All social agents are duty bearers for upholding the rights, security and dignity of our women and children.
Keywords: Exploitation - labour